The importance of assistance communication in the strategic direction and execution of projects - Silva Giraldo, Cesar Augusto; Mejia Jálabe, Aizar; Suarez, David Andrés (Universidad Francisco de Paula Santander, 2015)
The following article presents a reflection on the importance of assertive communi-cation in the strategic direction and execution of projects highlighting the importance of com-munication as a vital process and inherent part of the human being, is based ona series of authors who support from a existing communication practices of a positive or negative type, becoming a guiding element and that can be used assertively by managers in the different or-ganizations or work contexts, concepts such as assertiveness in communication seen as a social skill are also taken up. Means of which ideas, opinions and feelings are shown in a clear, direct, balanced, honest and respectful way, among others. Finally, the value of the management of assertive communication is mentioned as a vital tool that should be leveraged by the managers of the organizations from the planning and strategic direction in order to be able to guarantee competitive advantages, through the development of effective practices of leadership and totalintegration